Genetic factors affecting food-plant specialization of an oligophagous seed predator. - Laukkanen, L; Leimu, R; Muola, A; Lilley, M; Mutikainen, P (2013)
Several ecological and genetic factors affect the diet specialization of insect herbivores. The evolution of specialization may be constrained by lack of genetic variation in herbivore performance on different food-plant species. By traditional view, trade-offs, that is, negative genetic correlations between the performance of the herbivores on different food-plant species favour the evolution of specialization. To investigate whether there is genetic variation or trade-offs in herbivore performance between different food plants that may influence specialization of the oligophagous seed-eating herbivore, Lygaeus equestris (Heteroptera), we conducted a feeding trial in laboratory using four food-plant species. Although L. equestris is specialized on Vincetoxicum hirundinaria (Apocynaceae) to some degree, it occasionally feeds on alternative food-plant species. We did not find significant negative genetic correlations between mortality, developmental time and adult biomass of L. equestris on the different food-plant species. We found genetic variation in mortality and developmental time of L. equestris on some of the food plants, but not in adult biomass. Our results suggest that trade-offs do not affect adaptation and specialization of L. equestris to current and novel food-plant species, but the lack of genetic variation may restrict food-plant utilization. As food-plant specialization of herbivores may have wide-ranging effects, for instance, on coevolving plant-herbivore interactions and speciation, it is essential to thoroughly understand the factors behind the specialization process. Our findings provide valuable information about the role of genetic factors in food-plant specialization of this oligophagous herbivore.